H i Intensity Mapping Cross-correlation with Thermal Sunyaev–Zel’dovich Fluctuations: Forecasted Cosmological Parameter Estimation for FAST and Planck - Ayodeji Ibitoye; Furen Deng; Yichao Li; Yin-Zhe Ma; Yan Gong; Xuelei Chen (The Astrophysical Journal)
The 21 cm emission from neutral hydrogen surveys holds great potential as a valuable method for exploring the large-scale structure (LSS) of the Universe. In this paper, we forecast for the cross-correlation between the thermal Sunyaev–Zel’dovich (SZ) fluctuations as probed by the Planck satellite and fluctuations in the H i brightness temperature as probed by the ground-based Five-hundred-meter Aperture Spherical Telescope to trace the connection between galaxy clusters and the H i LSS. Assuming that the measurement is limited by instrumental noise rather than by foreground, we estimate the potential detectability of the cross-correlation signal and the improvement in the measurement of the H i cosmic density, the hydrostatic mass bias parameter, and the universal pressure profile parameters. We obtain a constraint on the cosmic neutral hydrogen density parameter significantly to σ (Ω _H I ) = 1.0 × 10 ^−6 . We also find that the average halo masses contributing to the H i − y cross-power spectrum in the one-halo regime is ∼1.5 × 10 ^14 M _⊙ . Our results also show that the H i –SZ cross-correlation has great potential to probe the distribution of neutral hydrogen (H i ) within halos at low redshift.